# SOLUTION: -1/4(x-8)+1/2(x+2)=x+15 (-1/4*x)-(-1/4*8)+(1/2*x)+(1/2*2)=x+15 -1/4x-2+1/2x+1=x+15 3/4x-1=x+15 (3/4x-3/4)-1=(x-3/4)+15 x-1=1/4x+15 And now I'm completely lost. Thanks for

Algebra ->  Algebra  -> Expressions-with-variables -> SOLUTION: -1/4(x-8)+1/2(x+2)=x+15 (-1/4*x)-(-1/4*8)+(1/2*x)+(1/2*2)=x+15 -1/4x-2+1/2x+1=x+15 3/4x-1=x+15 (3/4x-3/4)-1=(x-3/4)+15 x-1=1/4x+15 And now I'm completely lost. Thanks for       Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Expressions involving variables, substitution Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Expressions-with-variables Question 574688: -1/4(x-8)+1/2(x+2)=x+15 (-1/4*x)-(-1/4*8)+(1/2*x)+(1/2*2)=x+15 -1/4x-2+1/2x+1=x+15 3/4x-1=x+15 (3/4x-3/4)-1=(x-3/4)+15 x-1=1/4x+15 And now I'm completely lost. Thanks for any help you can give.Answer by Alan3354(30993)   (Show Source): You can put this solution on YOUR website!-1/4(x-8)+1/2(x+2)=x+15 (-1/4*x)-(-1/4*8)+(1/2*x)+(1/2*2)=x+15 -1/4x-2+1/2x+1=x+15 ************************-(-1/4*8) = +2 3/4x-1=x+15 ---------------- -1/4(x-8)+1/2(x+2)=x+15 (-1/4*x)-(-1/4*8)+(1/2*x)+(1/2*2)=x+15 -1/4x + 2 + 1/2x + 1 = x+15 (1/4)x + 3 = x+15 (1/4)x = x + 15 x = 4x + 60 -3x = 60 x = -20